Micropropagation of the medicinal plant Psychotria acuminata - Lara, Alfonso (2003)
Psychotria acuminata is a medicinal plant from which emetine, cephaeline, and psychotrine are extracted, to be used as expectorants and emetics. Nowadays, these alkaloids are extracted from wild plants because this species has not been domesticated as yet. Due to the potential use of its phytochemical principles and the small population of this species in the country, efficient tissue culture methods were developed for clonal and massive propagation of plants, collected in four different locations of Costa Rica. Multiple shoots were induced from axillary bud microcuttings and somatic embryos were induced from leaves, obtained from 5-cm plantlets growing in vitro in a Murashige & Skoog (1962) medium supplemented with 3 mg l-1 of BAP, 0.01 mg l-1 of NAA, 3% sugar and 2 g l-1 of phytagel. In vitro rooting was successfully achieved (100%) in shoots separated from the proliferating shoot cultures in MS/2 plus 6 mg l-1 of IAA. Since the root system generated in vitro dies once the plantlets are transferred to the substrate in the greenhouse, new roots were induced with Agriroot® 1 DP. After 8 weeks, acclimatization of 80% of the plantlets was achieved. This study provides additional evidence on the importance of the explant genotype for in vitro regeneration, since the multiplication rate, when using microcuttings as explants, as well as the timing for the morphogenetic events to occur, were different for each of the 3 sources of material, suggesting that plants from each location have a different genetic background.